2017
DOI: 10.18632/oncotarget.22565
|View full text |Cite
|
Sign up to set email alerts
|

miR-455-5p promotes cell growth and invasion by targeting SOCO3 in non-small cell lung cancer

Abstract: Non-small cell lung cancer (NSCLC) is the most common type of lung cancer. miR-455-5p has increased expression and the ability to promote tumorigenesis in certain cancers. However, the role of miR-455-5p in NSCLC has not been sufficiently investigated. SOCS3 (suppressor of cytokine signaling 3), an important tumor suppressor, is often aberrantly inactivated in various tumors, but it is currently unclear whether SOCO3 is a target of miR-455-5p. In the present study, we investigated the role of miR-455-5p in NSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 43 publications
1
29
0
Order By: Relevance
“…To the best of our knowledge, only one study indicated that miR-455-5p was differentially expressed between invasive and non-invasive breast cancer based on the analyses of archived FFPE tissues and laboratory-based barcoded cDNA library 46 . In other cancers, miR-455-5p has been reported as a potential oncogene for non-small cell lung cancer 47 , colon cancer 48 and oral squamous cancer 49 . In our present study, we confirmed these 4 screened DEmiRNAs not only differentially expressed in TNBC cell lines compared to normal breast cell line, but also showed effective regulation on cell proliferation and migration.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, only one study indicated that miR-455-5p was differentially expressed between invasive and non-invasive breast cancer based on the analyses of archived FFPE tissues and laboratory-based barcoded cDNA library 46 . In other cancers, miR-455-5p has been reported as a potential oncogene for non-small cell lung cancer 47 , colon cancer 48 and oral squamous cancer 49 . In our present study, we confirmed these 4 screened DEmiRNAs not only differentially expressed in TNBC cell lines compared to normal breast cell line, but also showed effective regulation on cell proliferation and migration.…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-455-5p acts as an oncogene in lung cancer. 25 In contrast, miR-455-5p exerts tumour-suppressive effects in prostate cancer. 26 However, the role of miR-455-5p in GBM has not been revealed.…”
Section: Overexpression Mir-455-5p Suppresses the Effect Of Lncrna mentioning
confidence: 99%
“…The expression level and activity of MMP2/9 have been revealed to be regulated by ERK1/2 in 293 and monocytic cells (53). In addition, aberrant miR-455-5p expression is partially regulated by activated ERK signaling in non-small cell lung cancer (54). It is possible that ERK1/2 regulates MMP2 by miR-455 in LNCaP cells.…”
Section: Discussionmentioning
confidence: 99%